Power plants and power systems control 2006 : a proceedings volume from the IFAC Symposium on Power Plants and Power Systems Control, Kananaskis, Canada, 2006 /: a proceedings volume from the IFAC Symposium on Power Plants and Power Systems Control, Kananaskis, Canada, 2006. (2007) - Unknown
No abstract available